Investigating the correlation of hip circumference to cardiovascular disease and type‐2 diabetes using Mendelian randomization - Hongtao Liu; Zhaoyu Li; Su Yan; Shaopeng Ming (Journal of Diabetes Investigation)
ABSTRACT Objective This study aimed to assess the correlation between hip circumference (HC) and the risk of cardiovascular disease (CVD) and type 2 diabetes mellitus using Mendelian randomization (MR) to overcome observational study limitations. Design MR analysis utilized genetic variation from the MR Base in a two‐sample analysis. Three methods were employed: MR‐Egger regression, weighted median estimator, and inverse variance weighting (IVW). Setting Data was acquired from MR Base, a platform summarizing genome‐wide association study (GWAS) data for MR research. Main Outcome Measures Publicly available summary statistics datasets from GWAS meta‐analyses were used, with HC and HC adjusted for body mass index (BMI) as exposures. Data for CVD and type 2 diabetes mellitus were obtained as outcomes. Results Results indicated a positive causal relationship between HC and CVD (IVW: P = 1.84e‐07, OR: 1.37, 95% CI: 1.22–1.54) as well as type 2 diabetes mellitus (IVW: P = 0.04, OR: 1.62, 95% CI: 1.02–2.56), independent of BMI. However, HC after BMI adjustment showed no significant causal relationship with CVD (IVW: P = 0.05, OR: 1.09, 95% CI: 1.00–1.19) and exhibited a negative association with type 2 diabetes mellitus (IVW: P = 0.00, OR: 0.76, 95% CI: 0.66–0.88), suggesting a protective effect against type 2 diabetes mellitus. Conclusions After adjusting for BMI, adipose tissue concentrated in the hip region showed a protective effect against type 2 diabetes mellitus but not against CVD. These findings offer insights into diabetes prevention and treatment strategies, and may inform plastic surgery procedures. Further research is needed to validate these findings and explore underlying mechanisms.